“Not just a drunk”: Eeyou drinking and agency in Chisasibi - Jacky Vallée (Drogues, santé et société, 2019)
Eeyou (Cree) people in Chisasibi, Quebec who engage in public drinking and drunkenness often have their behaviour and identity reduced to those of victims: victims of colonialism and assimilation attempts, victims of family violence, victims of addiction. Talking to the drinkers themselves is highly discouraged by fellow community members and often not considered by anthropological researchers. This ethnographic article is based on participant-observation and semi-formal interviews with adult women and men who self-identified as drinkers or former drinkers. It highlights the perspectives of people who currently engage, or have engaged in the past, in drinking behaviour that is perceived as “problematic” by their community and by social science researchers. Through a phenomenological approach, the concepts of lifeworlds and agency are used to illustrate how people actively engage with prominent community worldviews in thinking about their own behaviour and identities. Community members may refer to them as “drunks” or “zombies”. But these individuals refer to wider aspects of their identities and to their own agency in discussing their lives. As such, they appropriate identities as community members and claim their agency in spite of implications that they have forsaken these identities and this agency by engaging in extreme drinking. Il arrive souvent que le comportement et l’identité des Eeyous (Cris) de Chisasibi (Québec) qui consomment de l’alcool et sont ivres en public soient réduits à ceux de victimes : victimes de la colonisation et des tentatives d’assimilation, victimes de violence familiale, victimes de dépendances. Les autres membres de la communauté déconseillent fortement de s’adresser directement aux buveurs* et les chercheurs en anthropologie les ignorent la plupart du temps. Cet article ethnographique s’appuie sur l’observation participante et sur des entrevues semi-formelles effectuées auprès de femmes et d’hommes adultes qui se disent buveurs ou ex-buveurs. Il met en lumière le point de vue ...